5G for the connected world - Chandramouli, Devaki; Liebhart, Rainer; Pirskanen, Juho (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
'After the considerable success of LTE, why do we need a new system with a new radio and a new core? First, 5G will boost some of the LTE key performance indicators to a new horizon: capacity, latency, energy efficiency, spectral efficiency and reliability. We will describe the relevant radio and core features to enable optimizations (5G to be 10, 100 or 1000 times better than LTE) in these areas in respective chapters of the book'--
3.4.3 Contention-Based Access3.5 Radio Protocols; 3.5.1 Overall Radio Protocol Architecture; 3.5.2 Medium Access Control (MAC); 3.5.2.1 Logical Channels and Transport Channels; 3.5.2.2 MAC PDU Structures for Efficient Processing; 3.5.2.3 Procedures to Support UL Scheduling; 3.5.2.4 Discontinuous Reception and Transmission; 3.5.2.5 Random Access Procedure; 3.5.2.6 Beam Failure Management; 3.5.3 Radio Link Control (RLC); 3.5.3.1 Segmentation; 3.5.3.2 Error Correction Through ARQ; 3.5.3.3 Reduced RLC Functions for Efficient Processing; 3.5.4 Packet Data Convergence Protocol (PDCP)
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 11, 2019).
Keywords: Mobile communication systems -- Technological innovations; Broadband communication systems -- Technological innovations; Wireless sensor networks -- Technological innovations; Electronic books